NEW TRANSITION METAL OXALATO COMPLEXES WITH DABCOH22+ AS ADVERSE CATION: SYNTHESIS AND INFRARED STUDY - MAMADOU NDIAYE; ABDOULAYE SAMB; LIBASSE DIOP (Journal of Engineering Studies and Research)
On allowing DABCOH2(HC2O4)2 to react with transition metal dihalides in ethanol, a new series of complexes of general formula M(oxalate)2 DABCOH22+. nDABCOH22+.2X- (n=1/2;1) have been obtained. When (n=1) a dimeric structure is suggested, the two monomeric species being hold together by biprotonated DABCO through N-H…O hydrogen bonds. In the case of the complex M(oxalate)2DABCOH22+ .1/2 DABCOH22+.2X- -M = Ni, Cu- the structure is an infinite chain. The environment around the metallic centers is octahedral or square pyramidal. The oxalate behaves as a monochelating and hydrogen bonds involved ligand or is only concerned by hydrogen bonds.